Changes in blood physiological and biochemical parameters and intestinal flora in newborn horses and mares with angular limb deformities - Ma, Yuhui; Liu, Yigang; Li, Hai; Yang, Kailun; Yao, Gang (Frontiers in Veterinary Science, 2024)
IntroductionAngular limb deformities (ALDs) are a common skeletal development disorder in newborn foals. This condition affects the growth and development of foals and severely impacts their future athletic performance and economic value, causing significant financial losses to the horse industry. Placentitis, metritis, and severe metabolic diseases during mare pregnancy are significant causes of ALDs in newborn foals. It has been established that intestinal flora disorders can easily lead to inflammatory and metabolic diseases in the host. However, the incidence of ALDs in foals in Zhaosu County, Xinjiang, a key production area of China's horse industry, remains unclear. Additionally, the relationship between functional changes in foals with ALDs and their mares and changes in their intestinal flora is not well-understood.MethodsThis study investigated the status of ALD in newborn foals through clinical observation and imaging examinations. In addition, molecular biological methods were applied to examine the effects of ALDs foals and their mares on physiological and biochemical markers and gut microbiota.ResultsThe results showed that the incidence of ALD in Zhaosu area of China was 4.13%. In addition, by comparing and correlating the physiological and biochemical indicators and intestinal flora of foals and mares with ALD with those of healthy horses, it was found that foals and mares with ALD may promote the occurrence and development of the disease through the “blood marker changes-intestinal flora-ALDs” axis. In addition, by comparing the physiological and biochemical indicators and intestinal flora of foals and mares with ALD with the intestinal flora of healthy horses, it was found that the physiological and biochemical indicators and intestinal flora structure and metabolic pathways of foals and mares with ALD had significant changes.DiscussionThe diversity, species composition, and function of the intestinal flora of ALDs and their mares were significantly altered. These findings provide a scientific basis for understanding the etiology of ALDs in foals and offer new perspectives for diagnosing and treatment ALDs in newborn foals.